New genotypes and molecular characterization of Enterocytozoon bieneusi in captive black bears in China. (December 2019) - Huang, Xiaolong; Zhou, Ziyao; Liu, Haifeng; Deng, Lei; Bi, Bo; Chai, Yijun; Zhong, Zhijun; Hu, Yanchun; Fu, Hualin; Peng, Guangneng
Abstract: Enterocytozoon bieneusi, a common eukaryotic obligate intracellular parasite, can infect a wide range of hosts, including humans and domestic animals. There have been some reports of this organism in captive wildlife animals worldwide, but few studies have reported its detection in the captive black bears in Sichuan province of southwestern China. The present study was performed to determine the prevalence, genetic diversity, and zoonotic potential of E. bieneusi in captive Asiatic black bears from three farms in Sichuan province. Fecal specimens from Asiatic black bears in three farms were collected and analyzed for the prevalence of E. bieneusi . The overall prevalence of E. bieneusi was 18.7% (57/305) as determined by nested PCR amplification of the Internal Transcribed Spacer (ITS) gene on the rRNA of E. bieneusi, with the highest prevalence in the farm being 47.8% (44/92). Altogether, five genotypes of E. bieneusi were identified among the 57 E. bieneusi -positive samples, comprising three known genotypes (SC02, MJ2, and MJ5) and two novel genotypes named SCBB1 and SCBB2. Phylogenetic analysis showed that the genotypes SC02 and MJ2 were clustered into group 1 of zoonotic potential and that the genotypes MJ5, SCBB1, and SCBB2 were clustered into group 10. In conclusion, two known genotypes, SC02 and MJ2, were found to belong to the zoonotic potential group 1 and this evidence points to the fact that the E. bieneusi from these black bears could infect humans. Highlights: This is the first report of Enterocytozoon bieneusi infection in captive black bears in southwestern China. Five genotypes of Enterocytozoon bieneusi were identified. Two zoonotic genotypes (MJ2 and SC02) and two novel genotypes (SCBB1 and SCBB2) were identified.